2017
DOI: 10.1111/jen.12469
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally sustainable pest control options forDrosophila suzukii

Abstract: The spotted-wing drosophila or cherry vinegar fly (Drosophila suzukii) is native to Asia but has invaded other continents since 2008 and has spread throughout Europe. The females have a serrated ovipositor allowing them to penetrate the skins of intact ripening fruits to deposit their eggs, and the developing larvae rapidly destroy the fruits close to harvest. Drosophila suzukii has a rapid life cycle and the larvae develop well beneath the fruit surface. This means that the use of pesticides is problematic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 150 publications
0
44
0
1
Order By: Relevance
“…Insecticides have played a key role in the control of D. suzukii since its dispersal from Asia into new regions of the world (Schetelig et al, 2018). This has led to an increase or re-establishment of routine insecticide spray applications which disrupt integrated pest management (IPM) of other pests suppressed by biological control agents Medd, 2015, Roubos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Insecticides have played a key role in the control of D. suzukii since its dispersal from Asia into new regions of the world (Schetelig et al, 2018). This has led to an increase or re-establishment of routine insecticide spray applications which disrupt integrated pest management (IPM) of other pests suppressed by biological control agents Medd, 2015, Roubos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila suzukii is a widely distributed pest species, originally from Asia, and currently found in Europe (Calabria, Máca, Bächli, Serra, & Pascual, 2012;Cini, Ioriatti, & Anfora, 2012), North and South America (Bolda, Goodhue, & Zalom, 2010;Deprá, Poppe, Schmitz, De Toni, & Valente, 2014;Walsh et al, 2011) and able to invade new areas, where it has not been detected yet (Dos Santos et al, 2017). Recent studies reported the possibility of adopting the sterile insect technique (SIT) as a strategy to suppress D. suzukii populations, by itself or integrated to other techniques, such as biological control and Wolbachia (Garcia, Wollmann, Krüger, Schlesener, & Teixeira, 2017;Krüger et al, 2018;Lanouette et al, 2017;Nikolouli et al, 2017;Schetelig et al, 2017).…”
mentioning
confidence: 99%
“…Ovipositing D. suzukii females are difficult to detect and cause only little initial damage, making it difficult to discover the infestation early enough to respond effectively. Once the larvae start feeding inside the fruit they are protected from pesticides that are sprayed on the fruit [80]. Therefore, commercial soft fruit growers are now advised to repeatedly apply broad-spectrum insecticides in a prophylactic manner, until refined management practices are in place [81].…”
Section: Drosophila Suzukii-a New Invasive Pestmentioning
confidence: 99%